COMPARISON BETWEEN BIOMETRIC AND ELECTROLYTE LEAKAGE TESTS AS INDICATORS OF MAIZE SEED VIGOR - PEREIRA, LUCAS CAIUBI; CORREIA, LARISSA VINIS; SUAREZ, DAVID FERNANDO POSSO; CARVALHO, CRISTIANE DE; BRACCINI, ALESSANDRO LUCCA (International Journal of Maize & Sorghum, 2020)
The objective of this work was to compare the accuracy of seedling tests based on electrolyte release to distinguish different maize seed vigor levels with the accuracy provided by biometric tests for seedling length and biomass. For this purpose, seeds with different vigor levels of the Garra Viptera hybrid had their physiological potential evaluated through tests of germination, accelerated aging, seed electrical conductivity, field emergence, seedling length, seedling dry biomass, seedling electrical conductivity, potassium leakage and membrane injury index. Completely randomized design was used, with four replications, except for the field emergence variable, when the randomized complete block design was adopted. The obtained means were compared by Fisher's LSD test, at 5% probability, and then Pearson’s correlation coefficients were calculated between the tests based on seedling performance and the physiological quality results obtained with the seeds. In addition to their lower sensitivity to istinguish the different vigor levels, the biometric tests (length and biomass) showed values of correlation with field emergence considerably lower than those btained with the membrane permeability tests (seedling electrical conductivity, otassium leakage and membrane injury index). Among the tests based on electrolyte extravasation, the membrane injury index was the most accurate to differentiate maize seed lots in different vigor levels, as well as to estimate the seed emergence in the field.